DELL holds roundtable discussion on “The use of foreign English textbooks in the Malaysian education systems” - Ariffin, Adlina (Office of Corporate Communication, International Islamic University Malaysia, 2018)
On 9 January 2018, the IIUM’s Department of English Language and Literature (DELL), Kulliyyah of Islamic Revealed Knowledge and Human Sciences (KIRKHS) had the privilege of organising a roundtable discussion. It was on a very crucial and pertinent issue in the contemporary Malaysian education system which is the use of foreign English textbooks in the Malaysian schools.